Tree mapping and carbon inventory on a university campus in South Korea: Case study and global review - Songhee Lee; Woo Bin Park; Seungmin Lee; Jeong‐Min Lee; Yowhan Son; Tae Kyung Yoon (Ecosphere)
Abstract Campus trees have significant potential for sequestering carbon in urban environments and improving civic life quality; however, few inventories of university campus trees have been constructed worldwide (excluding North America). This study briefly overviews the current status, challenges, and prospects of inventorying campus trees and provides a case study of a campus tree inventory and carbon assessment through a student participatory program in South Korea. Campus tree maps from 25 universities in eight countries were investigated. A campus tree inventory usually consists of various data on the tree species, dbh, and biomass, and it is often prepared through a capstone or student project in the university. This review identified the following challenges: (1) Few cases have been reported outside North America, (2) publications and data sharing are limited, and (3) participants' experiences have not been evaluated. The case study on inventorying and mapping campus trees was performed by integrating drone‐based orthographic images and field censuses of tree data (species, diameter, GPS coordinates, etc.). A total of 2341 individual trees belonging to 73 species were surveyed over 28.7 ha of green spaces on campus, and various thematic maps were created online. In 2021, the aboveground carbon storage was 263.9 Mg C, and it increased annually by 5.62 Mg C. This study presents the first attempt to evaluate and report a campus tree carbon inventory at an East Asian university. Additional advancements in monitoring techniques and practices for campus trees may contribute to the sustainability of university campuses and local communities.